Comparison and Prediction of toxicity parameters of principal Aflatoxins, antimicrobial compounds and Antifungal Drugs by pKCSM server - Ferrari, I.V.; Mario, M. Di (International Journal of Scientific Research in Biological Sciences, 2022)
The purpose of this short study is to estimate the main toxicity properties of main Aflatoxins, Antimicrobial bio- compounds and Antifungal Drugs by pKCSM server. Several tests are performed, for instance AMES toxicity; Max. tolerated dose (human) (log mg/kg/day in units); Oral Rat Acute Toxicity (LD50) (mol/kg in units) Oral Rat Chronic Toxicity (LOAEL); Log mg/kg_bw/day in units);Hepatotoxicity; Skin Sensitisation; Pyriformis toxicity (log µg/L)and Minnow toxicity (log mM in units).